รูปแบบการออกอากาศของสถานีโทรทัศน์มหาวิทยาลัยบูรพาและ เครือข่ายสถาบันอุดมศึกษาภาคตะวันออก (โทรทัศน์สาธารณะ) - ดนตรี ฉัตรชัย; วิรุณราช บรรพต (Journal of Graduate School of Commerce-Burapha Review, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาเพื่อเสนอรูปแบบการออกอากาศของสถานีโทรทัศน์มหาวิทยาลัยบูรพา และเครือข่ายอุดมศึกษาภาคตะวันออก โดยใช้ระเบียบวิธีวิจัยเชิงคุณภาพ การเก็บข้อมูลด้วยการสนทนากลุ่ม จำนวน 2 ครั้ง เพื่อยืนยัน สำหรับกลุ่มตัวอย่างเลือกโดยวิธีเจาะจงกับตัวอย่างที่มีอำนาจตัดสินใจเรื่องสถานีโทรทัศน์แบ่งเป็น 3 กลุ่ม 1) ผู้บริหารมหาวิทยาลัย ได้แก่ อธิการบดี รองอธิการบดี ผู้รับผิดชอบงานทางด้านการวางแผน รองอธิการบดี ผู้รับผิดชอบงาน ทางด้านเครือข่ายอุดมศึกษา รองอธิการบดี ผู้รับผิดชอบงานทางด้านประชาสัมพันธ์ 2) ผู้ที่ได้รับมอบหมายในการประสานงาน เรื่อง สถานีโทรทัศน์มหาวิทยาลัยบูรพาและเครือข่าย ได้แก่ คณบดีวิทยาลัยพาณิชยศาสตร์ หัวหน้าภาควิชานิเทศศิลป์ หัวหน้าภาควิชานิเทศศาสตร์ หัวหน้างานประชาสัมพันธ์ และ 3) ผู้อำนวยการสถานีโทรทัศน์ ผลการวิจัย พบว่า รูปแบบการออกอากาศของสถานีโทรทัศน์มหาวิทยาลัยบูรพาและเครือข่ายอุดมศึกษาภาคตะวันออก ที่เป็นประโยชน์ต่อสาธารณะ คือ การออกอากาศผ่านอินเตอร์เน็ตและแอพลิเคชั่นบนมือถือ โดยมีประเด็นหลักทั้งสิ้น 8 ประเด็น ได้แก่ 1) กลุ่มเป้าหมาย คือ ผู้ปกครอง นิสิต นักศึกษา และประชาคมอาเซียน 2) การผลิตรายการเกี่ยวกับข่าว สารคดี ของแต่ละสถาบัน เศรษฐกิจชุมชน ให้นิสิตมีส่วนร่วมในการผลิตและเผยแพร่ผลงานวิจัย ภายใต้ระบบความละเอียดสูง 3) บุคคลากร ควรใช้บุคลากรที่มีความเชี่ยวชาญด้านเทคนิคการผลิต และมีความชำนาญทางด้านภาษาอังกฤษเป็นอย่างดี 4) งบประมาณ มหาวิทยาลัยต้องทำการหาเงินงบประมาณด้วยตนเองเช่นเดียวกับการหารายได้เลี้ยงมหาวิทยาลัย 5) การหารายได้ด้วยการทำความร่วมมือกับผู้ผลิตรายการ สถานีโทรทัศน์ การประชาสัมพันธ์กิจกรรมเพื่อสังคมของภาครัฐ และเอกชน และการขอรับบริจาคจากประชาชนและภาคเอกชน 6) แนวโน้มการรับชม พฤติกรรมผู้ชมนิยมการการรับ ชมย้อนหลังผ่านอินเตอร์เน็ต หรือแอพลิเคชั่นบนมือถือ 7) การเริ่มดำเนินการจากการทำรายการให้กับสถานีวิทยุโทรทัศน์ แห่งประเทศไทย สาธารณรัฐประชาธิปไตยประชาชนลาว แล้วจึงดำเนินการสถานีโทรทัศน์มหาวิทยาลัยบูรพาและ เครือข่ายอุดมศึกษาภาคตะวันออก ทั้งทางด้านโครงสร้าง ผังรายการ ตลอดจนแผนธุรกิจในภายหลัง 8) แผนในอนาคต ควรเพิ่มช่องทางดาวเทียม เคเบิล และดิจิตอลในภายหลัง TELEVISION BROADCASTING MODEL OF BUU CHANNEL & EASTERN HIGHER - EDUCATION NETWORK (PUBLIC TELEVISION) Chatchai Dontri and Banpot Wiroonratch Graduate School of Commerce Burapha University, Chon Buri 20131, Thailand This qualitative study was conducted with the aim to investigate the Television Broadcasting Model of Burapha University Channel and Eastern Higher - Education Network. The data were collected via a focus group interview which was conducted 2 rounds to guarantee the validity and reliability of the data. A purposeful sampling was used to recruit samples on the basis of their authority in making decision regarding TV station. The samples contained 3 groups; 1) university administrators including the president, the vice-president responsible for Planning, the vice-president responsible for the Higher-Education Network, the vice-president responsible for the Public Relations; 2) individuals assigned to coordinate the Burapha University Television Channel and Networks including the Dean of the Graduate School of Commerce, the Department Head of Visual Communication Art, the Department Head of Communication Arts, the Head of Public Relations; and 3) the television station director. The results revealed that the broadcasting model of Burapha Television Channel and Eastern Higher-Education Network beneficial to the public was the one over the Internet and on mobile applications. To enhance the capacity of the Channel, 8 main issues should be considered 1) the target audience is parents, students and ASEAN population; 2) the production involves news, documentary of each institute, news on community economy and the engagement of students in production and dissemination their research findings under the high – definition television; 3) personnel should have an expertise in technical production and have a good command of English; 4) the university finds its own Television Channel budget the same way as it raises the revenue for running the whole university; 5) raising fund should be done through collaborating with program producers and TV stations and through promoting public and private social activities; and also from asking for donations from the public and private sectors; 6) Trends of viewing behavior, audience prefers viewing re-aired programs on the Internet or the mobile applications; 7) the embarkation should begin with producing programs for the National Broadcasting Services of Thailand and the Loa People’s Democratic Republic, and later start the operation of the Burapha University Television Channel and Eastern Higher – Education Network in both the structure of TV programs and business plan; and 8) the future plans should include an addition of satellite, cable, and digital channels.